Lanatoside C decelerates proliferation and induces apoptosis through inhibition of STAT3 and ROS-mediated mitochondrial membrane potential transformation in cholangiocarcinoma - Zhang, Chao; Yang, Hong-Ying; Gao, Long; Bai, Ming-Zhen; Fu, Wen-Kang; Huang, Chong-Fei; Mi, Ning-Ning; Ma, Hai-Dong; Lu, Ya-Wen; Jiang, Ning-Zu; Tian, Liang; Cai, Teng; et al. (Frontiers in Pharmacology, 2023)
Introduction: The incidence of cholangiocarcinoma (CCA) has increased worldwide in recent years. Given the poor prognosis associated with the current management approach of CCA, new therapeutic agents are warranted to improve the prognosis of this patient population. Methods: In this study, we extracted five cardiac glycosides (CGs) from natural plants: digoxin, lanatoside A, lanatoside C, lanatoside B, and gitoxin. Follow-up experiments were performed to assess the effect of these five extracts on cholangiocarcinoma cells and compounds with the best efficacy were selected. Lanatoside C (Lan C) was selected as the most potent natural extract for subsequent experiments. We explored the potential mechanism underlying the anticancer activity of Lan C on cholangiocarcinoma cells by flow cytometry, western blot, immunofluorescence, transcriptomics sequencing, network pharmacology and in vivo experiments. Results: We found that Lan C time-dependently inhibited the growth and induced apoptosis of HuCCT-1 and TFK-1 cholangiocarcinoma cells. Besides Lan C increased the reactive oxygen species (ROS) content in cholangiocarcinoma cells, decreased the mitochondrial membrane potential (MMP) and resulted in apoptosis. Besides, Lan C downregulated the protein expression of STAT3, leading to decreased expression of Bcl-2 and Bcl-xl, increased expression of Bax, activation of caspase-3, and initiation of apoptosis. N-acetyl-L-cysteine (NAC) pretreatment reversed the effect of Lan C. In vivo, we found that Lan C inhibited the growth of cholangiocarcinoma xenografts without toxic effects on normal cells. Tumor immunohistochemistry showed that nude mice transplanted with human cholangiocarcinoma cells treated with Lan C exhibited decreased STAT3 expression and increased caspase-9 and caspase-3 expression in tumors, consistent with the in vitro results. Conclusion: In summary, our results substantiates that cardiac glycosides have strong anti-CCA effects. Interestingly the biological activity of Lan C provides a new anticancer candidate for the treatment of cholangiocarcinoma.